Mapping of Studies in Ergonomics Applied to the Hospital Context of the Professional Master’s Degree in Ergonomics at UFPE - Pessoa da Silva Cabral, Ana Karina; Marcelino , Juliana Fonsêca de Queiroz; Marçal , Márcio Alves (DAT Journal, 2025)
Hospital ergonomics involves the study of interactions between healthcare professionals, work tools and processes, furniture, equipment, and the physical environment, with the aim of adapting working conditions to human needs and limitations. The objective of this research is to present the mapping of studies in Ergonomics Applied to the Hospital Context of the Professional Master’s Degree in Ergonomics (PPErgo) of the Federal University of Pernambuco (UFPE). The search was carried out in the Institutional Repository of Theses and Dissertations of UFPE, from 2015 to 2025, with the descriptors Ergonomics and Hospital Environment. As a result, 22 dissertations linked to the two research lines of the program were found: Ergonomics and Usability of the Built Environment and Ergonomics and Usability of Products and Production. The main contributions of the research are recommendations for improvements in the physical, cognitive, and organizational spheres, directly impacting the quality of care and the health of workers.